Protection of the Peritoneal Membrane by Peritoneal Dialysis Effluent-Derived Mesenchymal Stromal Cells in a Rat Model of Chronic Peritoneal Dialysis - Lan Zhou; Ming Zong; Qiunong Guan; Gerald da Roza; Hao Wang; Hualin Qi; Caigan Du (Stem Cells International)
Peritoneal dialysis (PD) is a renal replacement option for patients with end-stage renal disease. However, a long-term exposure to hypertonic PD solutions leads to peritoneal membrane (PM) injury, resulting in ultrafiltration (UF) failure. This study was designed to primarily evaluate efficacy of PD effluent-derived mesenchymal stromal cells (pMSCs) in the prevention of PM injury in rats. The pMSCs were isolated from PD effluent. Male Wistar rats received daily intraperitoneal (IP) injection of 10 mL of Dianeal (4.25% dextrose) and were treated with pMSCs (1.2‐1.5×106/rat/wk, IP). UF was determined by IP injection of 30 mL of Dianeal (4.25% dextrose) with dwell time of 1.5 h, and PM injury was examined by histology. Apoptosis was quantitated by using flow cytometric analysis, and gene expression by using the PCR array and Western blot. Here, we showed that as compared to naive control, daily IP injection of the Dianeal PD solution for 6 weeks without pMSC treatment significantly reduced UF, which was associated with an increase in both PM thickness and blood vessel, while pMSC treatment prevented the UF loss and reduced PM injury and blood vessels. In vitro incubation with pMSC-conditioned medium prevented cell death in cultured human peritoneal mesothelial cells (HPMCs) and downregulated proinflammatory (i.e., CXCL6, NOS2, IL1RN, CCL5, and NR3C1) while upregulated anti-inflammatory (i.e., CCR1, CCR4, IL9, and IL-10) gene expression in activated THP1 cells. In conclusion, pMSCs prevent bioincompatible PD solution-induced PM injury and UF decline, suggesting that infusing back ex vivo-expanded pMSCs intraperitoneally may have therapeutic potential for reduction of UF failure in PD patients.